Noise Reduction and Gestational Age Estimation for Ultrasound Fetuses Images. - Kanger , Ebtesam F.; Kanger , Ebtesam F.; Hussein, Ahlam A. (Iraqi Journal of Science, 2022)
Ultrasound imaging is often preferred over other medical imaging modalities because it is non-invasive, non-ionizing, and low-cost. However, the main weakness of medical ultrasound image is the poor quality of images, due to presence of speckle noise and blurring. Speckle is characteristic phenomenon in ultrasound images, which can be described as random multiplicative noise that occurrence is often undesirable, since it affects the tasks of human interpretation and diagnosis. Blurring is a form of bandwidth reduction of an ideal image owing to the imperfect image formation process. Image denoising involves processing of the image data to produce a visually high quality image. The denoising algorithms may be classified into two categories, spatial filtering algorithms and transform domain based algorithms. In this work three adaptive filters are used to denoising speckle noise in ultrasonic (B-mode) images based on calculating the Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR) value as a metric is presented, then estimated the gestation age from filtered images using MATLAB program, as well as using Wiener filter to restore the degradation images.